Explosive Power Of Leg Muscles With Straight Kicks Of Anak Nagari Silat Athletes - Maulana, Zeno Triyuzi; Zulman, Zulman; Johor, Zainul; Roviandi, Riri (Yayasan Sekora, 2017)
The problem in this study is the low ability of straight kicks, this is thought to be influenced by explosive power. The purpose of this study was to determine how much the contribution of the explosive power of the leg muscles to the straight kicks of the Anak Nagari Pencak Silat athletes in Pesisir Selatan Regency. This research is classified as a correlational research conducted at the Anak Nagari Pencak Silat athletes in Pesisir Selatan Regency on October 20, 2019. The population of this research is the Anak Nagari Pencak Silat athletes in Pesisir Selatan Regency, totaling 20 people. This research sample taking using total sampling technique. The instrument used to obtain data regarding the explosive power of leg muscles is a standing broad jump, while to find out a straight kick a straight kick test is used in Pencak Silat. The hypothesis in this study is the contribution of leg muscle explosive power to the straight kick of the Anak Nagari Pencak Silat athletes in Pesisir Selatan Regency. Data analysis in this study using Product Moment correlation. The results of data processing in this study obtained rcount 0.748> rtabel 0.444, meaning that leg muscle explosive power had a significant relationship with straight kicks with a contribution of 55.95%. This shows that there is a significant relationship and contributes well between the power of the leg muscles to the straight kicks of the Anak Nagari Pencak Silat athletes in Pesisir Selatan Regency.